Nano-Vesicle Based Anti-Fungal Formulation Shows Higher Stability, Skin Diffusion, Biosafety and Anti-Fungal Efficacy In Vitro - Isaac G. Deaguero; Md Nurul Huda; Victor Rodriguez; Jade Zicari; Taslim A. Al-Hilal; Abu Zayed Md Badruddoza; Md Nurunnabi (MDPI AG, 2020)
Opportunistic fungal infections are responsible for over 1.5 million deaths per year. This has created a need for highly effective antifungal medication to be as potent as possible. In this study, we improved the efficacy of a common over the counter (OTC) antifungal skin medication, miconazole, by encapsulating nano-molecules of the drug in cholesterol/sodium oleate nano-vesicles. These nano-vesicles were characterized to optimize their size, zeta potential, polydispersity index and encapsulation efficiency. Furthermore, these nano-vesicles were compared to a conventional miconazole-based commercially available cream to determine potential improvements via permeation through the stratum corneum, cytotoxicity, and antifungal capabilities. Our results found that the vesicle size was within the nano range (~300 nm), with moderate polydispersity and stability. When compared with the commercially available cream, Actavis, as well as free miconazole, the miconazole nano-vesicle formulation displayed enhanced fungal inhibition by a factor of three or more when compared to free miconazole. Furthermore, with smaller nanoparticle (NP) sizes, higher percentages of miconazole may be delivered, further enhancing the efficacy of miconazole's antifungal capability. Cytotoxicity studies conducted with human dermal fibroblast cells confirm its biosafety and biocompatibility, as cell survival rate was observed to be twofold higher in nano-vesicle formulation than free miconazole. This formulation has the potential to treat fungal infections through increasing the retention time in the skin, improving the treatment approach, and by enhancing the efficacy via the use of nano-vesicles.